Study of maternal, fetal and neonatal outcomes in patients with gestational diabetes mellitus in a tertiary care hospital - Jadhav, Deepali S.; Wankhede, Uma N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: GDM is defined as carbohydrate intolerance of variable severity with onset or first recognition during pregnancy. Women with gestational diabetes are characterized by a relatively diminished insulin secretion and pregnancy induced insulin resistance primarily present in the skeletal muscle tissue. Normal pregnancy is a diabetogenic state characterized by exaggerated rate and amount of insulin release, associated with decreased sensitivity to insulin at cellular levels. The objective of the study was to study the maternal, the fetal and the neonatal outcomes of treated patients of GDM in present study. Methods: It was a hospital based clinical study. 1000 patients were enrolled between 24-28 weeks of gestation and DIPSI test was performed. Diagnosis of GDM was done using DIPSI criteria. 80 patients were diagnosed with GDM and followed till delivery to study the maternal, fetal and neonatal outcome. Results: Elderly patients, patients with previous history of GDM, patients with family history of diabetes, patients with high BMI and patients with polyhydramnios are at high risk for GDM. Conclusions: Hypertensive disorders and preterm birth are known to be higher with GDM are similar to the non-GDM group suggesting that early diagnosis and prompt treatment and maintaining strict glycemic control by patient may be beneficial. GDM can be managed well on MNT and lifestyle modifications, only few patients required insulin therapy. In spite of appropriate glycemic control, the incidence of macrosomia found to be high in GDM group. Sudden unexplained stillbirth can occur in spite of strict glycemic control. Neonatal complications have occurred despite well glycemic control.